Compulsory schooling reforms, education and mortality in twentieth century Europe - Gathmann, Christina; Jürges, Hendrik; Reinhold, Steffen (CESifo working papers, 2012)
Education yields substantial non-monetary benefits, but the size of these gains is still debated. Previous studies, for example, report contradictory effects of education and compulsory schooling on mortality - ranging from zero to large mortality reductions. Using data from 19 compulsory schooling reforms implemented in Europe during the twentieth century, we quantify the mean mortality effect and explore its dispersion across gender, time and countries. We find that men benefit from compulsory education both in the shorter and longer run. In contrast, compulsory schooling reforms have little or no effect on mortality for women. -- compulsory schooling ; education ; mortality ; Europe
Keywords: 1903-1976; Arbeitspapier; Graue Literatur; Bildungsökonomie